The impact of school lunches on school enrolment: Evidence from an exogenous policy change in India - Rajshri Jayaraman (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
Education is thought to be central to economic development. Yet, relatively little is known about how developing countries might advance school participation. In November, 2001 the Indian Supreme Court issued a remarkable interim order directing errant Indian states to other children in government primary schools a warm school lunch. This paper uses this exogenous policy change to evaluate the impact of school lunches on early primary school enrolment. It finds that the introduction of a school lunch is associated with a 25 per cent increase in class 1 enrolment. There is, however, no evidence to suggest that school lunches bridge the overall gender or caste gaps in enrolment.
Keywords: I2; O22; O12; 330; education; school lunches; quasi-natural experiment